Efficacy and safety of CT-P13 (biosimilar infliximab) in patients with rheumatoid arthritis: comparison between switching from reference infliximab to CT-P13 and continuing CT-P13 in the PLANETRA extension study. Issue 2 (29th April 2016) - Yoo, Dae Hyun; Prodanovic, Nenad; Jaworski, Janusz; Miranda, Pedro; Ramiterre, Edgar; Lanzon, Allan; Baranauskaite, Asta; Wiland, Piotr; Abud-Mendoza, Carlos; Oparanov, Boycho; Smiyan, Svitlana; Kim, HoUng; et al.
Abstract : Objectives: To assess the efficacy and safety of switching from the infliximab reference product (RP; Remicade) to its biosimilar CT-P13 (Remsima, Inflectra) or continuing CT-P13 in patients with rheumatoid arthritis (RA) for an additional six infusions. Methods: This open-label extension study recruited patients with RA who had completed the 54-week, randomised, parallel-group study comparing CT-P13 with RP (PLANETRA; NCT01217086 ). CT-P13 (3 mg/kg) was administered intravenously every 8 weeks from weeks 62 to 102. All patients received concomitant methotrexate. Endpoints included American College of Rheumatology 20% (ACR20) response, ACR50, ACR70, immunogenicity and safety. Data were analysed for patients who received CT-P13 for 102 weeks (maintenance group) and for those who received RP for 54 weeks and then switched to CT-P13 (switch group). Results: Overall, 302 of 455 patients who completed the PLANETRA study enrolled into the extension. Of these, 158 had received CT-P13 (maintenance group) and 144 RP (switch group). Response rates at week 102 for maintenance versus switch groups, respectively, were 71.7% vs 71.8% for ACR20, 48.0% vs 51.4% for ACR50 and 24.3% vs 26.1% for ACR70. The proportion of patients with antidrug antibodies was comparable between groups (week 102: 40.3% vs 44.8%, respectively). Treatment-emergent adverse events occurred in similar proportions of patients in the two groups during the extension study (53.5% and 53.8%, respectively). Conclusions: Comparable efficacy and tolerability were observed in patients who switched from RP to its biosimilar CT-P13 for an additional year and in those who had long-term CT-P13 treatment for 2 years. Trial registration number: NCT01571219; Results.